The Effect of Animated Instructional Media on Fourth-Grade Students' Mathematics Learning Outcomes in Roman Numerals - Desri Desri; Ahmad Rustam; Waode Ekadayanti (Journal of Education and Learning Sciences, 2025)
This study examined the effect of animated instructional media on fourth-grade elementary school students' mathematics learning outcomes in Roman numerals. It employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The study was conducted at SD Negeri 2 Konda with a sample of 55 students, comprising 29 students in the experimental class and 26 in the control class. Data were collected using achievement tests administered as a pretest and posttest. The data were analyzed through normality and homogeneity tests, hypothesis testing using an independent-samples t-test, and N-Gain analysis. The results showed that the experimental class achieved a mean posttest score of 84,79, which was higher than the control class mean of 73,34. Hypothesis testing yielded a significance value (Sig. 2-tailed) of 0,006 < 0,05; therefore, H₀ was rejected and H₁ was accepted. The N-Gain analysis further showed a mean improvement of 0,7533 in the experimental class, categorized as high, compared with 0,4446 in the control class, categorized as moderate. These findings indicate that animated instructional media had a significant effect on fourth-grade elementary school students' mathematics learning outcomes in Roman numerals.